Countdown for the New Basle Capital Accord: Are German banks ready for the internal ratings-based approach? - Ralf Ewert; Andrea Szczesny (Goethe University Frankfurt, Center for Financial Studies (CFS), 2001)
This paper uses a unique data set from credit files of six leading German banks to provide some empirical insights into their rating systems used to classify corporate borrowers. On the basis of the New Basle Capital Accord, which allows banks to use their internal rating systems to compute their minimum capital requirements, the relations between potential risk factors, rating decisions and the default probabilities are analysed to answer the question whether German banks are ready for the internal ratings-based approach. The results suggests that the answer is not affirmative at this stage. We find internal rating systems not comparable over banks and furthermore we reveal differences between credit rating determining and default probability determining factors respectively.
urn:nbn:de:hebis:30-9825
Keywords: G21; G33; G38; 330; Default probability; Credit rating; Bank regulation